2018
DOI: 10.2478/hjbpa-2018-0024
|View full text |Cite
|
Sign up to set email alerts
|

Botching Human Factors in Cybersecurity in Business Organizations

Abstract: Human factors remained unexplored and underappreciated in information security. The mounting cyber-attacks, data breaches, and ransomware attacks are a result of human-enabled errors, in fact, 95% of all cyber incidents are human-enabled. Research indicates that existing information security plans do not account for human factors in risk management or auditing. Corporate executives, managers, and cybersecurity professionals rely extensively on technology to avert cybersecurity incidents. Managers fallaciously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
73
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(75 citation statements)
references
References 27 publications
2
73
0
Order By: Relevance
“…Several reports have shown that humans are considered the greatest vulnerability to security (Schneier, 2004;Furnell and Clarke, 2012), which has been also confirmed by recent reports. One report estimated that 95% of cyber and network attacks are due to human errors (Nobles, 2018). In our context, humans are either computer system users or security analysts (King et al, 2018;Andrade and Yoo, 2019), though most research on this area focuses on errors done by computer system users.…”
Section: Human Cyber Security Errorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several reports have shown that humans are considered the greatest vulnerability to security (Schneier, 2004;Furnell and Clarke, 2012), which has been also confirmed by recent reports. One report estimated that 95% of cyber and network attacks are due to human errors (Nobles, 2018). In our context, humans are either computer system users or security analysts (King et al, 2018;Andrade and Yoo, 2019), though most research on this area focuses on errors done by computer system users.…”
Section: Human Cyber Security Errorsmentioning
confidence: 99%
“…Most of the research on cybersecurity has focused on improving computer network systems (Nobles, 2018), as many believe that information technology advances and software development is the main way to increase information security (Sadkhan, 2019;Benson and Mcalaney, 2020). Fewer studies have been conducted on enhancing cognitive capabilities and situational awareness of system analysts (D'Amico et al, 2005;Barford, 2010;Dutt et al, 2013;Knott et al, 2013;Tyworth et al, 2013;Mancuso et al, 2014;Gutzwiller et al, 2015;Aggarwal et al, 2018;Veksler et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The emergence of COVID 19 has created new complexities around cybersecurity and information security risk management (Suciu, 2020). Given the impact of new cybersecurity risks, there forms a critical need to create a cybersecurity culture that includes effective teams and processes that can address the emerging treats (Sousane, 2018;Nobles, 2018). The traditional approach taken by many organizations in safeguarding their information assets has been primarily to rely on technical controls such as hardware and software (Zuhdi, 2018).…”
Section: Setting Communications Expectationsmentioning
confidence: 99%
“…The traditional approach taken by many organizations in safeguarding their information assets has been primarily to rely on technical controls such as hardware and software (Zuhdi, 2018). However, in today's informationrisk work environments, technical controls alone are not sufficient to combat cybersecurity risks (Nobles, 2018). Organizational cybersecurity culture can be broadly described as a union of people (employees), processes, procedures, symbols, technology, training, awareness, commitment, and direct actions focused on sustaining cybersecurity within organizations (Zuhdi, 2018;Nobles, 2018).…”
Section: Setting Communications Expectationsmentioning
confidence: 99%
See 1 more Smart Citation